2009
DOI: 10.1203/pdr.0b013e3181a282a5
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 Normalizes Islet Vascularity in Intrauterine Growth Restricted Rats: Potential Role of VEGF

Abstract: Intrauterine growth restriction (IUGR) induced by uterine artery ligation in pregnant rats leads to low birth weight and early insulin secretory defects followed by the development of insulin resistance, decline in ␤-cell mass, and diabetes in adulthood. Neonatal administration of Exendin-4 (Ex-4) prevents the deterioration of ␤-cell mass and the onset of adult-onset diabetes. Our aim was to determine whether this effect occurs through preservation of islet vascularization. In 2 wk-old IUGR rats, endothelial-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 25 publications
5
42
0
Order By: Relevance
“…Interestingly, folate supplementation of protein-restricted dams, known to buffer against changes in DNA methylation (32), prevented the development of hypertension and reduced NO synthesis and endothelial dysfunction that was otherwise observed in male offspring (33,34). We hypothesize that the Gch1 down-regulation we observed with IUGR could play a role in the progressive ␤-cell decline that we have previously observed (9), through direct effects on the ␤-cells or islet vascularization (27).…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Interestingly, folate supplementation of protein-restricted dams, known to buffer against changes in DNA methylation (32), prevented the development of hypertension and reduced NO synthesis and endothelial dysfunction that was otherwise observed in male offspring (33,34). We hypothesize that the Gch1 down-regulation we observed with IUGR could play a role in the progressive ␤-cell decline that we have previously observed (9), through direct effects on the ␤-cells or islet vascularization (27).…”
Section: Discussionmentioning
confidence: 57%
“…8). Taken together, these changes and functional associations are suggestive of a deficient ␤-cell microenvironment in IUGR and may explain some of the ␤-cell phenotype observed in IUGR islets (3,6,27).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These phenomena restore chromatin structure at the PDX-1 promoter and prevent DNA methylation, thereby preserving PDX-1 transcription (Pinney et al 2011). In addition, Ex-4 normalizes islet vascularization in these animals (Ham et al 2009). The vascular bed plays an important role in normal pancreatic function, producing signals for differentiation and development, and delivering of nutrients to β-cells.…”
Section: Incretins and Metabolic Programming In Developmentmentioning
confidence: 93%
“…Intraislet vascular volume and endothelial cell vascular endothelial growth factor (VEGF) receptor abundance were reduced in LP-fed offspring and both were reversed by supplementation of the LP diet with taurine, an amino acid which normally is present at high concentrations within islets but which is depleted in animals exposed to a LP diet [7] . Islet vasculature is also diminished in other models of intrauterine growth retardation such as uterine artery ligation of the mother [8] and in that study, it was reversible by administration of the glucagon-like polypeptide-1 analog, exendin 4, to the offspring, presumably by increasing β-cell-derived VEGF which promoted local angiogenesis. We recently applied the LP diet model to the mouse and found that the β-cell regeneration that normally occurs in juveniles following depletion of β-cell mass with streptozotocin (STZ) treatment was prevented if the offspring had been previously exposed to a LP diet [9] .…”
Section: Topic Highlightmentioning
confidence: 64%